2012
DOI: 10.1007/s12471-012-0305-7
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in ventricular hypertrabeculation on cardiac MRI in elite football players

Abstract: A greater degree of LV hypertrabeculation is seen in healthy African athletes, combined with biventricular EF reduction at rest. Recognition of this phenomenon is necessary to avoid misdiagnosis of LVNC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 29 publications
1
26
0
1
Order By: Relevance
“…Interethnic differences were best measured in the entire cohort and attenuated to some extent in the reference groups where subgrouping led to under representation of specific ethnic or racial subgroups. The association between African background and increased trabeculation has been previously reported (2,6,19,20), but fractal analysis additionally shows a positive and negative association, respectively, between Hispanic and Chinese American participants with trabeculation.…”
Section: Regional Patterns and Reference Values For LV Trabeculationsupporting
confidence: 55%
See 1 more Smart Citation
“…Interethnic differences were best measured in the entire cohort and attenuated to some extent in the reference groups where subgrouping led to under representation of specific ethnic or racial subgroups. The association between African background and increased trabeculation has been previously reported (2,6,19,20), but fractal analysis additionally shows a positive and negative association, respectively, between Hispanic and Chinese American participants with trabeculation.…”
Section: Regional Patterns and Reference Values For LV Trabeculationsupporting
confidence: 55%
“…; and manuscript editing, G.C., F.Z., V.M., S.E.P., P.B., N.K.B., W.J.M., P.M.E., J.A.C.L., D.A.B., J.C.M. A bnormal trabecular patterns of the ventricular myocardium coexist with established cardiac disease (1)(2)(3)(4)(5), and a spectrum of so-called normal trabeculation with interethnic differences has also been observed in healthy hearts (2,6). Because of this large variability, trabecular phenotypes are hard to measure, but the recently described (3) fractal method applied to cardiac magnetic resonance (MR) imaging provides a sensitive mathematical solution.…”
Section: Author Contributionsmentioning
confidence: 99%
“…19 The same mechanism was also recently proposed to explain the high prevalence of J-point elevation in a population of patients with LV noncompaction cardiomyopathy. 20 An increased LV trabeculation is associated with physical training. In fact, a recent MRI study comparing soccer players of European versus African descent reported a greater degree of myocardial trabeculation in the latter.…”
Section: Discussionmentioning
confidence: 99%
“…In the current issue of this journal, Luijkx et al report the prevalence of hypertrabeculation in elite white and black athletes as seen at MRI [7]. They describe a greater degree of LV hypertrabeculation and lower LV and RV ejection fraction in elite black football players vs. white football players, which could be erroneously mistaken for NCCM.…”
mentioning
confidence: 99%
“…Echocardiographic views are operatordependent and off-axis views may affect the morphological assessment of myocardial trabeculations. However, excellent contrast of MRI, as used in the study by Luijkx et al, allows better visualisation of trabeculations, in particular when echocardiography windows are poor [7]. One MRI diagnostic criterion based on an end-diastolic ratio of compacted to noncompacted myocardium >2.3 in long-axis views was used for the diagnosis of NCCM [12].…”
mentioning
confidence: 99%